The transfer theorems for density of extreme values - Jokimaitis, Arvydas; Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2005)
In this paper the transfer theorems for density of minima and maxima of independent identically distributed random variables is proved.